2002
DOI: 10.1097/00003246-200206000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multifaceted, multidisciplinary, hospital-wide quality improvement program on weaning from mechanical ventilation

Abstract: A multifaceted, multidisciplinary weaning management program can change the process of care used for weaning patients from mechanical ventilation throughout an acute care hospital and across multiple services. This change can lead to large reductions in the duration of mechanical ventilation, length of stay, and hospital costs, even at a time when patients are sicker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 16 publications
0
48
1
3
Order By: Relevance
“…The percentage of patients who required weaning decreased from 80 to 10% when physician judgment was replaced by protocol management [119]. Protocol-directed daily screening of respiratory function and trials of SBT decrease the time required for extubation, the incidence of self-extubation, the incidence of tracheostomy and ICU costs, and results in no increase or even a decrease in the incidence of reintubation [6,26,[120][121][122][123][124][125][126]. In trauma patients, DRIES et al…”
Section: Weaning Protocolsmentioning
confidence: 99%
“…The percentage of patients who required weaning decreased from 80 to 10% when physician judgment was replaced by protocol management [119]. Protocol-directed daily screening of respiratory function and trials of SBT decrease the time required for extubation, the incidence of self-extubation, the incidence of tracheostomy and ICU costs, and results in no increase or even a decrease in the incidence of reintubation [6,26,[120][121][122][123][124][125][126]. In trauma patients, DRIES et al…”
Section: Weaning Protocolsmentioning
confidence: 99%
“…Several studies examined the interrelationship between physicians, nurses, and respiratory therapists and the effect on patient outcomes (Smyrnios et al, 2002;Stein-Parbury & Liaschenko, 2007). Education should not be limited to the nursing staff.…”
Section: The Effect Of Collaborative Practice and Teamwork On Patientmentioning
confidence: 99%
“…Ely and colleagues [5] have shown that a daily attempt at spontaneous ventilation reduces the mechanical ventilation period. Smyrnios and colleagues [6] concluded that it was of great importance to identify and resolve the patients' weaning problems quickly, which is possible through systematic medical access to an organised multidisciplinary system of work. The prolongation of mechanical ventilation can lead to an increased risk of ventilation-associated pneumonia [7,8]; on the other hand, premature extubation followed by reintubation can increase the morbidity and mortality [9].…”
Section: Introductionmentioning
confidence: 99%